Unterschiedliche Trends beim Fischnachwuchs der Nordsee - Dornheim, Holger; Wegner, Gerd (1998)
During this years’ International Bottom Trawl Survey (IBTS) of ICES, a total of 407 half hour tows were made in the North Sea including Skagerrak in January/ February, 1998. Results indicate except for sprat no outstanding incoming yearclasses for cod, haddock, saithe, Norway pout, whiting, herring, and mackerel. Most of the adult cod and saithe investigated did not show normal gonad development for this time of the year. The abundance of skates and sharks was still low. Results of 68 hydrographical stations of R.V. “Walter Herwig III” showed in contrast to four preceeding IBTS-surveys a warming of the northern North Sea of approx. 1 K. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010.